Emerging Trends in Cybersecurity for Health Technologies - Sanmorino, Ahmad (Jurnal Ilmiah Informatika Global, 2023)
The paper delves into the intricate relationship between technological advancements in healthcare and the pressing need for robust cybersecurity measures. It explores the escalating vulnerability of sensitive medical data due to the sector's digital transformation and the increased susceptibility to cyber threats. The interconnectedness of healthcare systems, from wearable devices to complex electronic health record systems, exposes healthcare organizations to relentless cyberattacks. Within this context, the article meticulously examines emerging trends and innovative solutions aimed at fortifying cybersecurity infrastructure and safeguarding sensitive medical data. It scrutinizes ten cybersecurity risks prevalent within the healthcare domain, highlighting the multifaceted nature of data security challenges faced by healthcare entities. Furthermore, the paper meticulously dissects ten AI-driven security mechanisms, ranging from behavioral analytics to AI-powered compliance management, showcasing their pivotal role in ensuring data integrity and confidentiality. Collaboration emerges as a pivotal strategy, with the article outlining ten collaborative initiatives that underscore the significance of joint efforts among healthcare institutions, technology providers, and cybersecurity experts. Collectively, these insights illuminate the imperative for proactive and adaptive cybersecurity strategies within the evolving landscape of healthcare technology integration.